Interest rate liberalization and debt risk in China - Song, Yuxuan (Вестник Томского государственного университета. Экономика)
Interest rate liberalization, which will have a multi-impact on the economy in the process of marketization, especially on the macro-debt market, is a requirement to develop the market economy. It is a current important economic topic that the risk control of the macro-debt market is related to the healthy degree of the economic de-velopment after the debt financing leverage turns to assets investment, and the study around these contents should be a cause for concern. As an important component of deepening financial reforms, the effect of interest rate liberalization on owners' opera-tions and management behavior of a micro-enterprise is prominent; on the other hand, the continuous climbing debt risk of local government will affect the financial deci-sions and implementation effect of enterprises by spillover effect. We made an empir-ical research on the extent of interest rate liberalization in China integrating relevant modes with the statistical data of PBC and our nation. Research on the reform in the Chinese financial market showed that prompting the reform of interest rate liberaliza-tion can obviously increase enterprises' financing capabilities which will be restrained by the aggravation of the local government's debt risk, and the significant enhance-ment of it enhances the impetus to enterprises' financing capabilities from interest rate liberalization.